Uniform cobalt nanoparticles embedded in hexagonal mesoporous nanoplates as a magnetically separable, recyclable adsorbent - Zhao, Can; Song, Yuexiao; Xiang, Tianyu; Qu, Wenxiu; Lou, Shuo; Yin, Xiaohong; Xin, Feng (Beilstein Journal of Nanotechnology, 2018)
Novel hexagonal nanoplates (NPLs) comprised of mesoporous carbon containing imbedded magnetic Co nanoparticles (CoAl2O4 phase) are prepared through direct carbonization of polydopamine (PDA)-coated CoAl layered double hydroxide (LDH). A uniform PDA coating initially covers the surface of LDH by dopamine self-polymerization under mild conditions. Well-dispersed Co nanoparticles are formed in the NPLs by the partial reduction of cobalt from Co2+ to Co0 with surface carbon during the heat treatment process. The surface morphology and specific surface area of the as-prepared NPLs can be tailored by adjusting the initial dopamine concentration and carbonization temperature. The mesoporous NPLs exhibit excellent sorption of rhodamine B (RhB) dye and fast magnetic separation in aqueous solution. Over 95% of RhB can be adsorbed within 2 min and the adsorption reaches equilibrium after about 30 min. The maximum adsorption capacity approaches 172.41 mg/g. After regeneration, this adsorbent can be recycled easily by magnetic separation and still possess good adsorption capacity for RhB removal, even after five cycles.
Keywords: absorbent regeneration; CoAl layered double hydroxide; efficient adsorbent; hexagonal nanoplates; magnetic nanoparticles; polydopamine

(untitled) - de Clippel, F.; Dusselier, M.; Van de Vyver, S.; Peng, L.; Jacobs, P. A.; Sels, B. F. (Green Chem., 2013)

(untitled) - Khan, M.; Tahir, M. N.; Adil, S. F.; Khan, H. U.; Siddiqui, M. R. H.; Al-warthan, A. A.; Tremel, W. (J. Mater. Chem. A, 2015)

(untitled) - Yan, Y.; Li, J.; Kong, F.; Jia, K.; He, S.; Wang, B. (Beilstein J. Nanotechnol., 2017)

(untitled) - Santhosh, C.; Velmurugan, V.; Jacob, G.; Jeong, S. K.; Grace, A. N.; Bhatnagar, A. (Chem. Eng. J., 2016)

(untitled) - Gómez-Pastora, J.; Dominguez, S.; Bringas, E.; Rivero, M. J.; Ortiz, I.; Dionysiou, D. D. (Chem. Eng. J., 2017)

(untitled) - Ma, Y.; Wang, Q.; Wang, X.; Sun, X.; Wang, X. (J. Porous Mater., 2015)

(untitled) - Dichiara, A. B.; Webber, M. R.; Gorman, W. R.; Rogers, R. E. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Gupta, V. K.; Kumar, R.; Nayak, A.; Saleh, T. A.; Barakat, M. A. (Adv. Colloid Interface Sci., 2013)

(untitled) - Mezohegyi, G.; van der Zee, F. P.; Font, J.; Fortuny, A.; Fabregat, A. (J. Environ. Manage., 2012)

(untitled) - Qin, Q.; Liu, Y.; Li, X.; Sun, T.; Xu, Y. (RSC Adv., 2018)

(untitled) - Asfaram, A.; Ghaedi, M.; Agarwal, S.; Tyagi, I.; Gupta, V. K. (RSC Adv., 2015)

(untitled) - Mady, A. H.; Baynosa, M. L.; Tuma, D.; Shim, J. J. (Appl. Catal., B: Environ., 2017)

(untitled) - Torad, N. L.; Hu, M.; Ishihara, S.; Sukegawa, H.; Belik, A. A.; Imura, M.; Ariga, K.; Sakka, Y.; Yamauchi, Y. (Small, 2014)

(untitled) - Yu, J.; Chen, G.; Sunarso, J.; Zhu, Y.; Ran, R.; Zhu, Z.; Zhou, W.; Shao, Z. (Adv. Sci., 2016)

(untitled) - Zhang, S.; Zhang, Y.; Jiang, W.; Liu, X.; Xu, S.; Huo, R.; Zhang, F.; Hu, J. (Carbon, 2016)

(untitled) - Lu, G.; Li, S.; Guo, Z.; Farha, O. K.; Hauser, B. G.; Qi, X.; Wang, Y.; Wang, X.; Han, S.; Liu, X.; DuChene, J. S.; Zhang, H.; et al. (Nat. Chem., 2012)

(untitled) - Jagadeesh, R. V.; Murugesan, K.; Alshammari, A. S.; Neumann, H.; Pohl, M. M.; Radnik, J.; Beller, M. (Science, 2017)

(untitled) - Wang, Q.; O'Hare, D. (Chem. Rev., 2012)

(untitled) - Yu, M.; Liu, R.; Liu, J.; Li, S.; Ma, Y. (Small, 2017)

(untitled) - Liu, Y.; Ai, K.; Lu, L. (Chem. Rev., 2014)

(untitled) - Zhang, X.; Wang, Y.; Dong, S.; Li, M. (Electrochim. Acta, 2015)

(untitled) - Mondal, A. K.; Kretschmer, K.; Zhao, Y.; Liu, H.; Wang, C.; Sun, B.; Wang, G. (Chem. – Eur. J., 2017)

(untitled) - Sun, H.; Cao, L.; Lu, L. (Nano Res., 2011)

(untitled) - Singh, K. P.; Gupta, S.; Singh, A. K.; Sinha, S. (Chem. Eng. J., 2010)

(untitled) - Chang, Y.-P.; Ren, C.-L.; Yang, Q.; Zhang, Z.-Y.; Dong, L.-J.; Chen, X.-G.; Xue, D.-S. (Appl. Surf. Sci., 2011)

(untitled) - Lu, W.; Wu, Y.; Chen, J.; Yang, Y. (CrystEngComm, 2014)

(untitled) - Liang, L.; Zhu, Q.; Wang, T.; Wang, F.; Ma, J.; Jing, L.; Sun, J. (Microporous Mesoporous Mater., 2014)

(untitled) - Geng, Z.; Lin, Y.; Yu, X.; Shen, Q.; Ma, L.; Li, Z.; Pan, N.; Wang, X. (J. Mater. Chem., 2012)

(untitled) - Zhao, C.; Guo, J.; Yang, Q.; Tong, L.; Zhang, J.; Zhang, J.; Gong, C.; Zhou, J.; Zhang, Z. (Appl. Surf. Sci., 2015)

(untitled) - Xie, Z.-L.; Huang, X.; Titirici, M.-M.; Taubert, A. (RSC Adv., 2014)

(untitled) - Kang, S. M.; Park, S.; Kim, D.; Park, S. Y.; Ruoff, R. S.; Lee, H. (Adv. Funct. Mater., 2011)

(untitled) - Qu, K.; Wang, J.; Ren, J.; Qu, X. (Chem. – Eur. J., 2013)

(untitled) - Liu, Z.; Ma, R.; Osada, M.; Iyi, N.; Ebina, Y.; Takada, K.; Sasaki, T. (J. Am. Chem. Soc., 2006)

(untitled) - Xiang, X.; Zhang, L.; Hima, H. I.; Li, F.; Evans, D. G. (Appl. Clay Sci., 2009)

(untitled) - Thommes, M.; Kaneko, K.; Neimark, A. V.; Olivier, J. P.; Rodriguez-Reinoso, F.; Rouquerol, J.; Sing, K. S. (Pure Appl. Chem., 2015)

(untitled) - Sun, L.; Tian, C.; Wang, L.; Zou, J.; Mu, G.; Fu, H. (J. Mater. Chem., 2011)

(untitled) - Wan, G.; Ma, M.; Jia, A.; Chen, L.; Chen, Y.; Cui, X.; Chen, H.; Shi, J. (J. Mater. Chem. A, 2016)

(untitled) - Ferrari, A. C.; Robertson, J. (Phys. Rev. B, 2000)

(untitled) - Zhang, G.; Lu, W.; Cao, F.; Xiao, Z.; Zheng, X. (J. Power Sources, 2016)

(untitled) - Zhang, M.; Uchaker, E.; Hu, S.; Zhang, Q.; Wang, T.; Cao, G.; Li, J. (Nanoscale, 2013)

(untitled) - Wu, Z.; Li, W.; Webley, P. A.; Zhao, D. (Adv. Mater., 2012)